The effect of combining post-partum yoga and pelvic floor training on life quality of post-partum mothers - Udayani, Ni Putu Mirah Yunita; Pramita Aswitami, Ni Gusti Ayu; Maryani, Ni Made Septiari (JNKI (Jurnal Ners dan Kebidanan Indonesia) (Indonesian Journal of Nursing and Midwifery), 2024)
Background: Data from the World Health Organization (WHO) indicate that the postpartum phase has the highest rates of maternal death and morbidity. In the first year following childbirth, almost 50% of women experience mental health issues and declining life quality scores on the physical-emotional dimension significantly. Objectives: This study aims to determine the effect of the combination of postpartum yoga and pelvic floor training on the life quality of postpartum mothers. Methods: This research was a Quasy Experimental Pre-Posttest Design of nonequivalent control groups which was conducted from February to August 2023 in Mengwi I Health Center, Badung Regency, Bali. The sample in this study consisted of 36 postpartum mothers in the control group and 36 postpartum mothers in the intervention group. Pre-data was in the form of quality of life before the intervention was given to the control and intervention groups and post-data was taken after the intervention was given and then data analysis was carried out using the Mann-Whitney test and the Wilcoxon test. Results: The results showed that the mean value of the increase in life quality scores in the intervention group was greater than the control group. In the 1st domain (physical healthiness) there was a significant difference between the two groups after study (p-value = 0.000). In the 2nd domain (psychological well-being) there was a significant difference between the two groups after study (p-value = 0.000). In the 3rd domain (social relationship) there was a significant difference between the two groups after study (p-value = 0.000). In the 4th domain (environmental dimension) there was a significant difference between the two groups after study (p-value = 0.000). Lastly, in the 5th domain (general healthiness) there was a significant difference between the two groups after study (p-value = 0.000). Conclusions: There is an increase in the life quality of postpartum mothers after being given a combination of postpartum yoga and pelvic floor training.